The National Police of Ukraine activities in the sphere of ensuring national security - A. A. Nikitin (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the study of theoretical and practical issues of organisation and legal support of the National Police in the field of national security of Ukraine. The relevance of the chosen topic has been substantiated and a general analysis of the state of scientific research on this issue has been carried out. The regulatory and legal acts and scientific sources which make up the content of the National Police's activities in the field of ensuring national security of Ukraine have been analysed. The essence of the theoretical provisions of the scientific categories “security”, “national security”, “security and defence sector entities”, “National Police”, “legal regulation”, as well as the practice of their consolidation in legislation have been investigated. It has been provided the author's understanding of the concept of national security as a state of protection of the state sovereignty, constitutional order, public order, economic, scientific, technical and defence potential, information sphere and state secrets from external and internal threats, from any manifestations of unlawful encroachments, which is achieved by applying a system of measures of political, economic, organisational, legal, military, ideological and other nature, proportionate to the threats to the national interests of Ukraine.